2015
DOI: 10.1038/srep10985
|View full text |Cite
|
Sign up to set email alerts
|

Slippage in stacking of graphene nanofragments induced by spin polarization

Abstract: Spin polarization and stacking are interesting effects in complex molecular systems and are both presented in graphene-based materials. Their possible combination may provide a new perspective in understanding the intermolecular force. The nanoscale graphene structures with zigzag edges could possess spin-polarized ground states. However, the mechanical effect of spin polarization in stacking of graphene nanofragments is not clear. Here we demonstrate the displacement between two stacked rhombic graphene nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…During unloading, the whole system will return to the initial minimum energy state. Possibility of this type of mechanically activated slippage in bilayer graphene was suggested by first-principles calculations. , Additional first-principles calculations investigated the stacking configuration change due to the presence of electric field, spin polarization, and quantum confinement effects. To our best knowledge, our study is the first report on the recoverable interlayer slippage observed in experiments and MD simulations.…”
Section: Results and Discussionmentioning
confidence: 73%
“…During unloading, the whole system will return to the initial minimum energy state. Possibility of this type of mechanically activated slippage in bilayer graphene was suggested by first-principles calculations. , Additional first-principles calculations investigated the stacking configuration change due to the presence of electric field, spin polarization, and quantum confinement effects. To our best knowledge, our study is the first report on the recoverable interlayer slippage observed in experiments and MD simulations.…”
Section: Results and Discussionmentioning
confidence: 73%
“…As the applied AFM indentation forces were larger than %3000 nN, the elastic stiffness of our double-layer graphene ribbons softened. Possible reasons for the softening of the elastic stiffness include large AFM indentation force-induced interlayer sliding between graphene layers, [35][36][37][38] larger AFM indentation force-induced geometrical dislocation and distortion of graphene ribbons, delamination of graphene ribbons away from the SiO 2 surface of the Si mass or the trench edges, and crack formations in the graphene ribbons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the high-symmetry stackings, the low-symmetry ones deserve systematic researches [262][263][264][265][266][267][268][269][270][271][272][273][274][275]. A sliding bilayer graphene (BLG), with various misalignment configurations, is chosen for the detailed discussions about the specific essential properties.…”
mentioning
confidence: 99%